Risk Factors of Inadequate Colposcopy After Large Loop Excision of the Transformation Zone: A Prospective Cohort Study. Issue 1 (January 2018) - Carcopino, Xavier; Mancini, Julien; Gondry, Jean; Chevreau, Julien; Lamblin, Gery; Atallah, Anthony; Lavoue, Vincent; Caradec, Claire; Baldauf, Jean-Jacques; Bryand, Angélique; Henno, Sebastien; Agostini, Aubert; et al.
Abstract : Objective: The aim of the study was to identify the risk factors of post–large loop excision of the transformation zone (LLETZ) inadequate colposcopy. Materials and Methods: From December 2013 to July 2014, a total of 157 patients who had a LLETZ performed for the treatment of high-grade intraepithelial lesion with fully visible cervical squamocolumnar junction were included. All procedures were performed using semicircular loops. The use of colposcopy made during each procedure was systematically documented. Dimensions and volume of LLETZ specimens were measured at the time of procedure, before formaldehyde fixation. All participants were invited for a follow-up colposcopy 3 to 6 months after LLETZ. Primary end point was the diagnosis of post-LLETZ inadequate colposcopy, defined by a not fully visible cervical squamocolumnar junction and/or cervical stenosis. Results: Colposcopies were performed in a mean (SD) delay of 136 (88) days and were inadequate in 22 (14%) cases. Factors found to significantly increase the probability of post-LLETZ inadequate colposcopy were a history of previous excisional cervical therapy [adjusted odds ratio (aOR) = 4.29, 95% CI = 1.12–16.37, p = .033] and the thickness of the specimen (aOR = 3.12, 95% CI = 1.02–9.60, p = .047). The use of colposcopy for the guidance of LLETZ was statistically associated with a decrease in the risk of post-LLETZ inadequate colposcopy (aOR = 0.19, 95% CI = 0.04–0.80, p = .024) as the achievement of negative endocervical margins (aOR = 0.26, 95% CI = 0.08–0.86, p = .027). Conclusions: Although the risk of post-LLETZ inadequate colposcopy is increased in patients with history of excisional therapy and with the thickness of the excised specimen, it could be reduced with the use of colposcopic guidance and the achievement of negative endocervical margins. Abstract : The risk of post–large loop excision of the transformation zone inadequate colposcopy is increased in patients with history of excisional therapy and with the thickness of the excised specimen.